SISTEM PAKAR DIAGNOSIS DINI PENYAKIT LEUKIMIA MENGGUNAKAN METODE FORWARD CHAINING(STUDI KASUS (RSUD) RADEN MATTAHER JAMBI) - Huda Aminnudin, Fattachul; Gunawan, Satria (JURNAL AKADEMIKA, 2020)
Research and development carried out on Leukemia aims to produce an alternative in handling leukemia which has been carried out by doctors. This research methodology uses a waterfall model with steps 1). Analyzing the System, 2). System Design, 3). Input, Process and Output, 4). Program Testing, 5). Product Results and Revisions, 6). Final Products, 7 ). Product Dissemination, also supported by data flow diagrams that illustrate the description of the system being built. This research resulted in an application of an expert system in handling web-based leukemia. This application is designed using PHP and MySQL programming languages with several display designs that make it easy for users to use it as a tool in detecting leukemia before being treated by a doctor.